Telecentres as Promoters of Digital Citizenship Amongst Poor Populations in Belo Horizonte, Brazil - Haddad, Samir R.; Oliveira, A.; Beaufils, A. (15th International Conference of Education, Research and Innovation (ICERI2022), 2022)
In the current information society, over half the world’s population still does not have access to the Internet. This problem strikes mostly elderly people, poor people, people with little schooling, dwellers in rural areas, and affects women more than men. Scant access to Information and Communication Technologies (ICTs) makes the exercise of citizenship difficult and generates social exclusion. For this reason, policies of digital inclusions have been promoted. We address what has been done in Belo Horizonte, Brazil, where the implemented programmes make available spaces called “Telecenters”, equipped with computers connected to the Internet, of free public access, located in communities of poor people. In this study, the main goal is to understand how citizenship, net society, ICTs and telecentres are perceived by the disadvantaged people who use them in Belo Horizonte. Data were collected from semi structured focus groups, held in five telecentres, with 32 participants, men and women, between 18 and 70 year of age, poor people with a low level of schooling. To feel more prepared to participate in society as active citizens, participants acknowledge, on the one hand, the need to access information freely and to get ICTs training and, on the other hand, the key role that digital inclusion programmes plays to achieve these goals. From the results obtained, one infers that telecentre effectively stimulate the exercise of citizenship and that, in this way, they are relevant to eschew social and digital exclusion. A set of indicators regarding participants’ perceptions emerged from the qualitative analysis.